Musa × parahaekkinenii (Musaceae): A new artificial interspecific hybrid from Kerala, India - Smisha, Komban Parameswaran; Sabu, Mamiyil (Bangladesh Journal of Plant Taxonomy, 2018)
Musa × parahaekkinenii (Musaceae), a new manually crossed interspecific hybrid of two wild parent plants Musa coccinea Andrews (female) and Musa haekkinenii N.S. Lý & Haev. (male), is described and illustrated. A comparison of characters with its parents and a key to the new hybrid M. × parahaekkinenii are provided.